Determining the Effect of Social and Academic Support on STEM Confidence and Learning Environment Among Female Engineering Students in Pakistan - Mujtaba, Aiza; Lashari, Tahira Anwar; Anwar Lashari , Sana; Khan Khattak, Muazzam Ali; Mujtaba, Khubaib; Mujtaba, Musfera (Journal of Technical Education and Training, 2023)
Gender inclusion and female participation in STEM courses have always been challenging in a patriarchal country like Pakistan. Women are often underrepresented in engineering fields, as engineering fields are usually considered manly. Female students confront many challenges, be it workplace or educational institutes. Some of the self-perceived and determined challenges are discussed in this study. As determined through this research study, factors affecting female participation are low STEM confidence, Gender disparity, Social and Academic Support, and Learning Environment. Empirical Evidence is collected using a questionnaire with 25 items based on the Likert scale. The dependent variables are STEM Confidence and Learning Environment, whereas the independent variables are Social and Academic Support. Participants included 170 female UG and PG engineering students from 4 universities in Pakistan. Data were collected through the Questionnaire, which included an online survey. Correlation method and statistical test MANOVA were applied, using SPSS 21 to determine the effect of social and academic support on the STEM confidence of female students and to find a relationship between the variables. Results indicate a positive correlation between the variables STEM confidence and social and academic Support and Learning environment, whereas a slight correlation has been observed between social Support and LE. MANOVA results indicated a significant effect of Social and Academic Support on the STEM confidence of female students. Empirical Evidence shows that Social and academic support can affect the STEM of female engineering students, and the LE of females can also be affected by social and academic Support.